Surveillance of community-acquired viral infections due to respiratory viruses in Rhone-Alpes (France) during winter 1994 to 1995. - Lina, B (1996)
Nasal swab from patients with acute flu-like illness were evaluated for the presence of respiratory viruses in the Rhone-Alpes region of France from 1 October 1994 through 2 May 1995. The relative frequencies and seasonal distributions of the specific viruses were assessed. In addition, virus type was correlated with specific clinical signs and symptoms. During the study, 962 samples were collected by 75 medical practitioners participating in the Groupe Regional d'Observation de la Grippe surveillance network. One or more viruses were detected from 348 samples (36.1%), including 108 respiratory syncytial virus (RSV), 64 influenza virus A type H3N2, 47 influenza virus B, 64 coronavirus, 35 rhinovirus, 22 adenovirus, 5 enterovirus, and 3 parainfluenza-fluenza strains. There were 16 mixed infections. RSV infections peaked in the early winter, and influenza viruses A and B infections peaked during the late winter and early spring. There were two peaks of coronavirus infections (late fall and late winter). Other viruses were detected at lower levels throughout the study period. Patients from whom adenovirus was isolated were significantly more likely to have a fever of > 39.5 degrees C than were patients with other detectable viruses (P < 0.001). Furthermore, there was a significant correlation between influenza and cough (P < 0.01) and RSV and bronchiolitis (P < .001). Thus, the current study defined the overall and relative frequencies of respiratory virus detection from nasal swab specimens in patients with an acute flu-like illness in the Rhone-Alpes region of France during a 7-month period. Correlation with clinical signs and symptoms and provisional conclusions regarding seasonality were also determined.